Ekplorasi Polemik Lima Hari Sekolah; Aktor, dan Kontestasi - Saiful Bahri; Dede Setiawan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The Five-Day School or Full Day School (FDS) policy, as regulated in Ministerial Regulation No. 23 of 2017, has sparked controversy among the public, particularly within Islamic boarding schools (pesantren) and religious organizations. This study aims to identify the key actors involved in the opposition to this policy and analyze the fundamental reasons behind the resistance. Using a qualitative hermeneutic approach and historical causal analysis, the study reveals that Nahdlatul Ulama (NU) and the pesantren community were the primary actors opposing the FDS policy, whereas the government and Muhammadiyah tended to support it, citing character education enhancement. The findings indicate that the pesantren community's rejection was rooted in Islamic legal principles, particularly dar’ul mafasid muqaddamun ‘ala jalbil mashalih (preventing harm takes precedence over obtaining benefits). Pesantren leaders argue that the policy threatens the existence of madrasah diniyah and reduces students' religious education opportunities. Furthermore, the government is perceived as having failed to consider schools' infrastructure readiness and the psychological impact on students, which could diminish the effectiveness of learning. Resistance to this policy evolved into a social movement, marked by mass demonstrations from the pesantren community and advocacy efforts by NU. This study concludes that the FDS controversy extends beyond education policy debates, reflecting a broader contestation between educational modernization and the preservation of traditional values. Therefore, a more flexible and inclusive policy approach is recommended, taking into account school readiness and engaging various stakeholders, including religious organizations and education practitioners, to ensure that the policy is widely accepted and does not trigger social resistance.